Solve the given system using elimination.
![Solve the given system using elimination class=](https://us-static.z-dn.net/files/d63/458664b25728830a9e8fda2047039156.gif)
Answer:
s = -1
r = 2
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
Equality Properties
Algebra I
Step-by-step explanation:
Step 1: Define Systems
2r + 8s = -4
7r = -6s + 8
Step 2: Rewrite Systems
2r + 8s = -4
Step 3: Redefine Systems
-7r = 28s + 14
7r = -6s + 8
Step 4: Solve for s
Elimination
Step 5: Solve for r
Answer:
r = 2, s = - 1
Step-by-step explanation:
Given the 2 equations
2r + 8s = - 4 → (1)
7r = - 6s + 8 ( add 6s to both sides )
7r + 6s = 8 → (2)
Multiplying (1) by 7 and (2) by - 2, then adding will eliminate the r- term
14r + 56s = - 28 → (3)
- 14r - 12s = - 16 → (4)
Add (3) and (4) term by term to eliminate r , that is
44s = - 44 ( divide both sides by 44 )
s = - 1
Substitute s = - 1 into either of the 2 equations and solve for r
Substituting into (1)
2r + 8(- 1) = - 4
2r - 8 = - 4 ( add 8 to both sides )
2r = 4 ( divide both sides by 2 )
r = 2
solution is r = 2 , s = - 1